Indeks Kepuasan Masyarakat Terhadap Pelayanan Publik di Unit Pengelola Rumah Susun pada Dinas Perumahan dan Gedung Pemerintah Provinsi Daerah Khusus Ibukota Jakarta - MEISYA KUSUMANINGTYAS; Budi Setiyono; Lusia Astrika (Journal of Politic and Government Studies, 2018)
Public services are now things that can not be separated from society's lives. One of public service organized by Jakarta Capital City Government is the public service in Flats Management Unit on Department for Housing and Building of Jakarta Capital City Government. Through Flats Management Unit of Special Capital Region of Jakarta, Jakarta Capital City Government has implemented the public service to the society in the form of implementation of residential management or the use of flats.One of its objectives is the achievement of public satisfaction. The service activities provided by Flats Management Unit of Special Capital Region of Jakarta will be assessed based on the level of public satisfaction. Therefore, through this study, author wanted to measure and know the Index of Public Satisfaction of Flats Management Unit of Special Capital Region of Jakarta based on the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform No. 16 of 2014 about the Guidelines of Public Satisfaction Surveys on Public Service Delivery with reference to 9 (nine) indicators used to measure public satisfaction index.Researcher used descriptive quantitative method by spreading questionnaires to 150 respondents. From the result of data analysis, the researcher got the Cumulative Value of Public Satisfaction Index of 75.15 therefore the performance of the Flats Management Unit of Special Capital Region of Jakarta can be categorized as well. Currently, there are still deficiencies in the implementation of flats service at Flats Management Unit of Special Capital Region of Jakarta in terms of service procedures and infrastructure facilities.Recommendations that can be given is such as Flats Management Unit of Special Capital Region of Jakarta can improve the shortcomings based on complaints submitted by the society, and can maintain or expected to improve the quality of existing services in order to achieve the objectives of the public services implementation.Keywords: Flats, Public Satisfaction Index, Public Services, Special Capital Region of Jakarta.